Aspects Related to the Influence of Christianity on the Society - Mihai Handaric (RIRAI Publisher, 2021)
In this paper the author analyzes the influence of Christianity on society. There will be demonstrated that through its structure, man was created to live in the community. He discovers himself by relating to the world surrounding him, as it is argued by Martin Heidegger, and Martin Buber. Here we also include the relationship with the transcendent. The philosophical and sociological arguments help us understand the influence Christianity had on European society. The religion of the European nations had a strong influence on the civilization of the continent and the world. Researchers have come to the conclusion that man was created with an innate religious feeling. Rudolf Otto sought to demonstrate that man's religious experience can only be explained by the aprioric existence of the sacred. So did Mircea Eliade, who introduced a new term